2005
DOI: 10.1007/s00535-005-1651-7
|View full text |Cite
|
Sign up to set email alerts
|

Self-expandable metallic stent placement for palliation in gastric outlet obstructions caused by gastric cancer: a comparison with surgical gastrojejunostomy

Abstract: Self-expandable metallic stent placement is a safe and efficacious procedure for palliation, with shorter operating time and more prompt restoration of oral intake, compared to surgical alternatives in patients with GOO caused by gastric cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
75
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 114 publications
(84 citation statements)
references
References 24 publications
2
75
0
1
Order By: Relevance
“…Finally, stent placement in the distal duodenum has the advantage that malignant biliary obstruction occurring after duodenal stent placement is not precluding the possibility to perform biliary drainage by endoscopic retrograde cholangiopancreatography (ERCP) at a later time point. Biliary obstruction occurs in 2-8 % of patients after stent placement in the proximal duodenum [1,2,20,21]. It is often difficult or even impossible to cannulate the papilla through the mesh of an uncovered stent.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, stent placement in the distal duodenum has the advantage that malignant biliary obstruction occurring after duodenal stent placement is not precluding the possibility to perform biliary drainage by endoscopic retrograde cholangiopancreatography (ERCP) at a later time point. Biliary obstruction occurs in 2-8 % of patients after stent placement in the proximal duodenum [1,2,20,21]. It is often difficult or even impossible to cannulate the papilla through the mesh of an uncovered stent.…”
Section: Discussionmentioning
confidence: 99%
“…Nine articles met the eligibility requirements and were included in the review (Fig. 1) [12][13][14][15][16][17][18][19][20]. All included articles were retrospective, single-institution case series, except for one [19] that included a prospective collection of patient-reported outcomes for a subset of patients using a questionnaire ( Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…One study reported specifically the absence of symptoms in 13.2% of non-curatively managed patients [13]. An additional 3 of the 9 studies reported that all patients had unresectable, symptomatic gastric outlet obstruction (GOO) requiring palliation [14][15][16].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations